2018
DOI: 10.1371/journal.pone.0200960
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of reef shark abundance and biomass in the Solomon Islands

Abstract: Remote island nations face a number of challenges in addressing concerns about shark population status, including access to rigorously collected data and resources to manage fisheries. At present, very little data are available on shark populations in the Solomon Islands and scientific surveys to document shark and ray diversity and distribution have not been completed. We aimed to provide a baseline of the relative abundance and diversity of reef sharks and rays and assess the major drivers of reef shark abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Environmental factors such as temperature, depth and habitat composition are also key drivers of elasmobranch assemblages 31,78,79 , but these drivers had little or no contribution in our study. Based on our results, there was a positive effect of depth on both elasmobranch species richness and abundance, which is consistent with findings from other studies 19,80 . Changes in temperature, light level and productivity associated to depth may explain some of the observed trends in elasmobranch assemblages 78 .…”
Section: Discussionsupporting
confidence: 93%
“…Environmental factors such as temperature, depth and habitat composition are also key drivers of elasmobranch assemblages 31,78,79 , but these drivers had little or no contribution in our study. Based on our results, there was a positive effect of depth on both elasmobranch species richness and abundance, which is consistent with findings from other studies 19,80 . Changes in temperature, light level and productivity associated to depth may explain some of the observed trends in elasmobranch assemblages 78 .…”
Section: Discussionsupporting
confidence: 93%
“…These findings align with those of related BRUV studies: a study of tropical sharks on the Great Barrier Reef found proximity to reefs with high coral cover to be the most important factor structuring shark communities and a factor contributing to MPA success [12], while a previous analysis of the fish community in the Betty’s Bay MPA found habitat affected the diversity and species composition while protection had no effect [27]. However, in cases where fishing has had large impacts on populations of sharks and their prey, MPA presence can explain the most variation in shark abundance and community composition compared to environmental and habitat variables alone [49,50]. Our expanded analysis of chondrichthyan abundance and richness did find a limited positive effect of protection in Betty’s Bay not previously detected [27].…”
Section: Discussionmentioning
confidence: 99%
“…South Africa’s endemic catsharks may not be currently threatened, but their abundance in the region is supported by the quality of habitat located in Betty’s Bay, indicating even small MPAs could play a role in protecting coastal ecosystems and endemic species. Spatial protection has had strong effects on resident populations of more threatened sharks on tropical reefs [49,50]; thus MPAs will likely play an important conservation role for endemic South African species should fishing pressure or habitat degradation intensify.…”
Section: Discussionmentioning
confidence: 99%
“…Baited remote underwater video stations (BRUVS) are increasingly being used to survey predator abundances on coral reefs [11][12][13]. BRUVS have been shown to have higher statistical power and consistency than unbaited videos [14].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in rainfall between seasons can impact freshwater output, turbidity, and nutrient loads which may impact coastal species abundances including elasmobranchs [ 18 , 19 ]. Many BRUVS studies compare locations that are sampled at a single time point [ 12 , 20 ]. By only having a single sampling period, it is not possible to document if community composition and abundance estimates change seasonally.…”
Section: Introductionmentioning
confidence: 99%